Berberine Inhibits Uterine Leiomyoma Cell Proliferation via Downregulation of Cyclooxygenase 2 and Pituitary Tumor-Transforming Gene 1. (July 2017) - Chuang, Tung-Yueh; Min, Jie; Wu, Hsiao-Li; McCrary, Cristina; Layman, Lawrence C.; Diamond, Michael P.; Azziz, Ricardo; Al-Hendy, Ayman; Chen, Yen-Hao
We previously demonstrated that berberine (BBR) inhibits cell proliferation and induces apoptosis in a human uterine leiomyoma (UtLM) cell line but does not demonstrate a significant cytotoxic effect in a normal human uterine smooth muscle (UtSM) cell line. However, the mechanisms of this inhibition are unclear. Of note, cyclooxygenase 2 (COX2) and pituitary tumor-transforming gene 1 (PTTG1) are overexpressed in human uterine leiomyomata and are involved in the pathogenesis of uterine fibroids (UFs). We found that COX2 and PTTG1 were overexpressed in UtLM and that BBR decreased COX2 and PTTG1 expression in UtLM cells. Our data support that UtLM and UtSM are immortalized cell lines without phenotypic alterations from parental cell types and suggest that COX2 and PTTG1 are molecular targets for BBR. However, studies in these cell lines may not reveal all activities of BBR in vivo, and we therefore proceeded to test in this report the antitumor effects of BBR in an UF nude mouse xenograft model. When UF nude mice were killed at 7 weeks, tumor weight in controls was 45 ± 7 mg versus 20 ± 3 mg ( P < .05) in the low-dose (5 mg/kg) and 7 ± 3 mg ( P < .01) in the high-dose (10 mg/kg) BBR groups, respectively. Expression of proliferation markers, cell cycle–related genes, and UF-related genes was downregulated in tumors. No unusual behavioral changes and no signs of kidney or liver damage were observed in the animals with BBR treatment. In conclusion, our data suggests that (a) COX2 and PTTG1 are molecular targets for BBR and (b) BBR is potentially an effective and safe anti-UF agent.